Crapemyrtle Bark Scale: A New Threat for Crapemyrtles, a Popular Landscape Plant in the U.S. - Zinan Wang; Yan Chen; Mengmeng Gu; Erfan Vafaie; Michael Merchant; Rodrigo Diaz (Insects, 2016)
Crapemyrtle bark scale, Acanthococcus (=Eriococcus) lagerstroemiae (Kuwana) (Hemiptera: Eriococcidae), is a newly introduced insect pest on crapemyrtles, Lagerstroemia spp. (Myrtales: Lythraceae), one of the most popular flowering shrubs in the U.S. Since first detected in Texas in 2004, this pest has spread to twelve states causing losses to stakeholders. To develop a management plan, we reviewed current knowledge about the pest’s biology and ecology, and suggested research approaches including studying its thermal tolerance, host range, plant resistance and biological control. Parasitoids and predators have been reared from A. lagerstroemiae in the U.S. and China. However, new surveys of natural enemies should be conducted in China, and studies on the host range and impacts of natural enemies on A. lagerstroemiae may help determine the potential for classical biological control. The life history, preying efficiency and rearing methods are important for coccinellid predators found in the U.S. including Chilocorus cacti L. and Hyperaspis spp. To enhance natural enemy performance, it is important to evaluate a sustainable insecticide program that considers efficacy, timing, rate and impact on pollinator health. Finally, an integrated management program of A. lagerstroemiae is discussed including planting resistant cultivars, using host specific natural enemies, and prudent use of insecticides.